The resilience of individuals with a heart disease (Research, Society and Development, 2022)
Resilience is presented as a contemporary health issue still under construction, inserting itself in a new health paradigm, which privileges the healthy resources of the individual. This study aimed to investigate the process of resilience in individuals with heart disease. Quantitative cross-sectional study conducted in September and October 2019 in a Brazilian institution of high complexity in cardiology. The sample consisted of 51 heart disease. The Connor-Davidson Resilience Scale (CD-RISC) was used. In the statistical analysis, the IMB Software SPSS Statistics version 26.0 was used. Logistic regression was used to verify the presence of association between the dependent variable (resilience) and the independent variables, and logistic regression was used to analyze the strength of the association between the variables. Resilience was identified in most individuals. There was no significant association of resilience and other variables, but it is possible to infer that some factors influence the resilience process.